Charmed scalar mesons masses within the QCD sum rules framework - Lozéa,A. (2007)
In this work, we evaluate the D+sJ(2317), D(0)0(2308), D(0)0(2407) and D+0(2403) masses. These are scalar mesons recently discovered in the BABAR, BELLE and FOCUS Collaborations. The nature of these particles is intensely discussed nowadays. We treat them as a diquark-antidiquark configuration and treat the problem using the QCD sum rules (QCDSR) approach.